2009
DOI: 10.1007/s10562-009-9976-0
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Benzene to Phenol by Al2O3-Supported Fe(III)-5-Sulfosalicylic Acid (ssal) Complex

Abstract: Selective oxidation of benzene with H 2 O 2 to phenol has been developed using a novel Fe(III) complex bearing 5-sulfosalicylic acid ligands immobilized alumina catalyst under visible light irradiation. The catalyst activity was evaluated by the photooxidation of benzene to phenol. The results indicate the best result with 100% conversion of benzene and 27.64% selectivity for phenol at low catalyst loading (0.7 mmol/g alumina). The catalyst was used for at least 4 cycles without any appreciable loss of activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…These functional groups indicate the presence of carbon in the Al 2 O 3 films. 36 The broad band that appeared at 3670 cm −1 is due to the surface-bonded hydroxyl groups (O−H), which play an important role in the growth of Al 2 O 3 ALD films. 37 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…These functional groups indicate the presence of carbon in the Al 2 O 3 films. 36 The broad band that appeared at 3670 cm −1 is due to the surface-bonded hydroxyl groups (O−H), which play an important role in the growth of Al 2 O 3 ALD films. 37 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this observation and the results of our earlier experiments [16], a reasonable mechanism for the photocatalytic degradation DNBP, in the Fe(III)-ssal-Al 2 O 3 /H 2 O 2 system under visible light irradiation is outlined in Fig. 10.…”
Section: Postulated Reaction Mechanismmentioning
confidence: 53%
“…In our recent study [16], we reported a novel kind of catalyst, [Fe(III)-ssal]-Al 2 O 3 , made by supporting the complex Fe(III) 5-sulfosalicylic acid (ssal) onto Al 2 O 3 . This Al 2 O 3 supported Fe(III) complex having 5-sulfosalicylic acid (ssal) ligand was found to be an efficient catalyst for the direct hydroxylation of benzene with hydrogen peroxide under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 1117 is ascribed to the functional group of Al‐O‐Al . In addition, the carbonyl group (C‐O) has appeared at 1250 cm −1 , and the CO group at 1710 cm −1 , indicating the presence of carbon in the Al 2 O 3 films . The band at 3670 cm −1 is attributed to the surface‐bonded hydroxyl groups (O‐H), which play an important role in the growth of Al 2 O 3 ‐grown ALD films .…”
Section: Resultsmentioning
confidence: 99%